الرقابة على مشروعية الملاحقات الجنائية الدولية: دراسة تحليلية في ضوء التوتر بين العدالة والسيادة (Journal of Academic Research, 2026)
This study addresses the issue of oversight of the legitimacy of international criminal prosecutions, by analyzing the legal and practical frameworks governing the jurisdiction of the International Criminal Court (ICC), in light of the tension between international criminal justice and national sovereignty.The study finds that although the Court is subject to multiple oversight mechanisms, it faces serious challenges, including politicization, selectivity, and lack of cooperation.Through the case studies of Sudan and Libya, the research reveals the complexity of balancing justice and sovereignty in practice.Finally, several recommendations are offered to enhance the legal legitimacy of the Court’s actions and to promote a more effective balance between justice and state sovereignty.